Minsky's Analysis, the European Single Currency, and the Global Financial System - Malcolm Sawyer (Levy Economics Institute of Bard College, 1999)
The paper begins with a brief review of the main ideas associated with Hyman Minsky and their implications for economic policy and the achievement of full employment. There is a focus on the financial instability hypothesis, the role of the central bank as lender of last resort, and the requirements for regulation of the financial system. The implications of these ideas for economic policy are then explored at the level of the European Union and the global economy. It is argued that the Minsky analysis would suggest that at the level of the nation state, the general drift of economic policy and changes in institutional arrangements have made the prospects for full employment bleak. For the European Union, the institutions that are emerging in the context of EMU and the euro are considered in terms of their impacts on the level of economic activity. At the global economy level, the need for international institutions to regulate the global financial system is considered.
Keywords: 330